Biochemical characterization of the interactions between doxorubicin and lipidic GM1 micelles with or without paclitaxel loading - Leonhard, Victoria (2015)
Doxorubicin (Dox) is an anthracycline anticancer drug with high water solubility, whose use is limited primarily due to significant side effects. In this study it is shown that Dox interacts with monosialoglycosphingolipid (GM1) ganglioside micelles primarily through hydro-phobic interactions independent of pH and ionic strength. In addition, Dox can be incorporated even into GM1 micelles already containing highly hydrophobic paclitaxel (Ptx). However, it was not possible to incorporate Ptx into Dox-containing GM1 micelles, suggesting that Dox could be occupying a more external position in the micelles. This result is in agreement with a higher hydrolysis of Dox than of Ptx when micelles were incubated at alkaline pH. The loading of Dox into GM1 micelles was observed over a broad range of temperature (4°C–55°C). Furthermore, Dox-loaded micelles were stable in aqueous solutions exhibiting no aggregation or precipitation for up to 2 months when kept at 4°C–25°C and even after freeze–thawing cycles. Upon exposure to blood components, Dox-containing micelles were observed to interact with human serum albumin. However, the amount of human serum albumin that ended up being associated to the micelles was inversely related to the amount of Dox, suggesting that both could share their binding sites. In vitro studies on Hep2 cells showed that the cellular uptake and cytotoxic activity of Dox and Ptx from the micellar complexes were similar to those of the free form of these drugs, even when the micelle was covered with albumin. These results support the idea of the existence of different nano-domains in a single micelle and the fact that this micellar model could be used as a platform for loading and delivering hydrophobic and hydrophilic active pharmaceutical ingredients.